Efficacy of intranasal administration of formalin-killed Pasteurella haemolytica A2 against intratracheal challenge in goats - Effendy, A.W.M.; Zamri-Saad, M.; Puspa, R.; Rosiah, S. (British Veterinary Associationadminoff@bsava.com, 1998)
A trial was conducted to compare the efficacy of intranasal vaccination in protecting goats against pneumonic pasteurellosis with intramuscular vaccination using an oil adjuvant vaccine, and a combination of the two methods. Forty goats were divided into four equal groups. Group 1 was vaccinated twice intranasally with formalin-killed Pasteurella haemolytica A2, group 2 was vaccinated twice intramuscularly with an oil adjuvant vaccine containing P haemolytica A7, and group 3 was initially vaccinated intranasally with the formalin-killed P haemolytica A2 followed by intramuscular vaccination with the oil adjuvant vaccine. In each group the two vaccinations were carried out four weeks apart. Group 4 was the unvaccinated control group. All goats were challenged intratracheally with 4 ml of an inoculum containing live P haemolytica A2 at a concentration of 1.3 x 107 colony forming units/ml two weeks after the last vaccination and were killed 14 days after the challenge. Although group 2 showed the highest clinical score following the challenge, deaths were observed only in group 3. Three goats in group 1 had pneumonic lung lesions, compared with six goats in group 2 and all the goats in groups 3 and 4. The lung lesions in group 1 were significantly (P < 0.05) less severe than in groups 3 and 4. Similarly, the lesions in group 2 were markedly less severe than in groups 3 and 4, although the differences were not significant. The difference between the extent of the lung lesions in the goats in groups 1 and 2 was not significant. Antibody against P haemolytica A2 in group 1 reached peak levels and was significantly (P < 0.01) higher than in the control group one week after the second vaccination, before declining.